17: OBESE ADIPOCYTE-DERIVED EXOSOMAL MIRNAS TARGETING TGF-β SIGNALING ARE ASSOCIATED WITH POOR ASTHMA CONTROL. Issue 3 (March 2016) - Epstein, S; Ferrante, S; Nadler, E; Barberio, M; Golberg, M; Maltz, L; Hubal, M; Freishtat, R
Abstract : Purpose of Study: Obesity is a major risk factor for difficult-to-control asthma. We reported obese visceral adipose-derived exosomes contain miRNAs capable of impairing TGF-β signaling, a pathway involved in airway remodeling, associated with poor asthma clinical outcomes. We hypothesized that adipose-derived exosomal miRNAs from obese youth with asthma would be associated with poor asthma control. Methods Used: AsthMaP-2 Subjects (youth with physician-diagnosed asthma) were selected at extremes of obesity (n=10) and leanness (n=10). We profiled RNA from adipose-derived exosomes from serum and urine and identified significant correlations (p⩽0.05) between obese adipose-derived exosomal miRNAs and Asthma Control Test (ACT) scores. Ingenuity Pathway Analysis generated predicted mRNA targets and pathways. Summary of Results: Obese subjects had a BMI≥98th percentile and lean subjects had a BMI⩽13th percentile for age and sex. Serum adipose-derived exosomes contained 12 ACT-correlated miRNAs predicted to target 2, 963 mRNAs with TGF-β Signaling as the top pathway (ratio=36/87; p=3×10 −9 ). Urinary adipose-derived exosomes contained 7 ACT-correlated miRNAs predicted to target 2, 387 mRNAs with TGF-β Signaling among the top pathways (ratio=18/87; p=0.01). The serum exosomal miRNAs were predicted to target TGF-β signaling mediators' mRNAs: downregulation of ACVR2B, SMAD3, SMAD5, and SMAD7 by miR-15a-5p (Fold Change (FC)=1.5; p=0.039) and upregulation of TGFB2 and TGFBR2 by miR-153-3p (FC=−1.7; p=0.041). The urinary exosomal miRNAs were also predicted to target TGF-β signaling mediators' mRNAs, the net effects were the opposite direction: upregulation of ACVR2B and SMAD4 by miR-138-5p (FC=−1.2; p=0.033) and downregulation of TGFB2 and TGFBR2 by miR-153-3p (FC=1.6; p=0.026) and SMAD6 by miR-3187-5p (FC=2.3; p=0.008). Conclusions: Poor asthma control in obese youth is associated with adipose-derived exosomal miRNAs in both serum and urine, in particular those that are predicted to affect TGF-β signaling. Due to anatomic considerations, visceral adipose-derived exosomes are expected to predominate in urine, while serum will contain a mix of both visceral and subcutaneous adipose-derived exosomes. Therefore, adipose-derived exosomes derived from urine may be useful biomarkers in obese subjects with asthma.